2006
DOI: 10.1300/j157v06n02_03
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Medicinal Herbs by Diabetic Jordanian Patients

Abstract: Diabetes mellitus is the most common metabolic disorder worldwide. To date, there have been no reports on the frequency of use of herb medicines in the managements of diabetes mellitus in Jordan. This cross-sectional study was conducted by interviewing 310 diabetic patients visiting two medical centers in Jordan: Jordan University of Science & Technology Medical Center and Sarih Medical Center between December 2003 and August 2004. It is found that 31% of interviewed patients have used herbal products (96 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
2
21
3
Order By: Relevance
“…In the current study, 56AE7% of study participants reported that they told their physicians and nurses about using CAM. This finding is different from other studies (Moolasarn et al 2005, Otoom et al 2006, Arıkan et al 2008). The healthcare professionals should establish an open dialogue that will lead to a clear distinction between harmful and possibly helpful CAM therapies (Jankovic et al 2004).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In the current study, 56AE7% of study participants reported that they told their physicians and nurses about using CAM. This finding is different from other studies (Moolasarn et al 2005, Otoom et al 2006, Arıkan et al 2008). The healthcare professionals should establish an open dialogue that will lead to a clear distinction between harmful and possibly helpful CAM therapies (Jankovic et al 2004).…”
Section: Discussioncontrasting
confidence: 88%
“…Parents were also asked whether or not they had discussed alternative medicine with their children's paediatrician or nurse. Answers were categorised according to the precedents from previously published literature (Lee et al 2004, Kumar et al 2006, Otoom et al 2006, Arıkan et al 2008, Ozturk & Karayag ız 2008, Akyol et al 2011.…”
Section: Instrument and Data Collectionmentioning
confidence: 99%
“…Some patients (20%) experienced adverse effects, such as hypoglycaemia and hyperglycaemic coma, which could be caused by medicinal plants. A study carried out in Jordan showed side effects in 36.5% of patients using herbal medicine to treat diabetes [19]. This information does not prove that medicinal plants are responsible for this but this is an alert which must urge scientists to investigate the side effects of medicinal plants in general, and antidiabetic plants, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies mentioned alternative medicine-related toxicity in diabetic patients [13][14][15] . Mostly observed side effects are headache, nausea, vomiting, palpitations and sweating [16] .…”
Section: Discussionmentioning
confidence: 99%